Ligand-mediated electron transfer in pH-tolerant Mn(II)/Fe(VI) bimetallic system: High-valent iron-oxo generation for efficient antibiotic removal - Jia-Xuan Ou-Yang; Xin-Jia Chen; Yu-Kun Huang; Jia-He Guo; Pi-Jun Duan; Xin-Yi Zhang; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ming-Jie Huang; Ying Shao; Xiao-Wei Xu; et al. (Water Research, 2027)

Making waves: Rethinking membrane technologies for water remediation from a full-chain application perspective - Jing Wang; Chang-Wei Bai; Xin-Jia Chen; Zhi-Quan Zhang; Yu-Kun Huang; Xiao-Wei Xu; Pi-Jun Duan; Jin-Song Guo; Fei Chen (Water Research, 2026)

Fruit allergens and their allergenicity reduction: characteristics, technologies, and prospects - Tanying Zhang; Jinshen Chu; Yuntong Ying; Haochen Ye; Mengxian Li; Yiran Xie; Haozhe Yi; Jing Che; Bowen Li; Binjia Zhang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

High-surface-area g-C3N4/ZIF-8 heterojunction for synergistic radical and non-radical photocatalytic peroxymonosulfate activation toward antibiotic degradation: Mechanistic insight and membrane application - Ying-Ying Zhang; Si-Han Guo; Wu-He Ji Pi; Qing-Tong Dong; Qi Huang; Jing Bu; Li-Xuan Kou; Chun Li; Quan-Liang Chen (Journal of Environmental Chemical Engineering, 2026)

CAH-VAE: Channel-aware hierarchical VAE for hyperspectral image compression - Huiwen Wang; Mi Wang; Yingdong Pi; Jing Xiao (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Hydrogeochemical constraints on the genesis, fluid mixing, and heavy metal mobilization of low-temperature geothermal systems in the Mufushan granite batholith, South China - Linxin Li; Zhengqing Wu; Lei Wang; Jian Ou; Jing Pi; Sheng Liu; Lala Wei; Liuqin Huang; Hongchen Jiang; Yanlong Dong (Geothermics, 2026)

A Novel Cancer Driver Genes Identification Method Based on Self-Supervised Dual Masked Graph Autoencoder - Pi-Jing Wei; Xinhao Guo; Wenjun Li; Yun Ding; Rui-Fen Cao; Zhenyu Yue; Kanglin Wang; Chun-Hou Zheng (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Atomically dispersed Ruδ+-Ov-Ce3+ interfaces enable photothermal synergy-driven dry reforming of methane via a CH3O⁎ intermediate-mediated pathway - Fei Wang; Shule Liu; Jianfeng Lu; Jing Ding; Jing Xiao; Yunhong Pi; Weilong Wang (Chemical Engineering Journal, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

Research progress on the characteristics of milk allergens and the effect of Maillard reaction and its assistance treatment on allergenicity - Xiaowen Pi; Tanying Zhang; Jia Cao; Zeyu Peng; Bowen Li; Haozhe Yi; Wanxiang Guo; Jing Che; Chen Wang; Jinshen Chu (Food Chemistry, 2026)

Self-sustaining singlet oxygen Fenton-like catalysis for scalable water remediation - Fu-Qiao Yang; Chang-Wei Bai; Jing Wang; Xin-Jia Chen; Pi-Jun Duan; Zhi-Quan Zhang; Ying Shao; Meng Zhang; Fei Chen (Chemical Engineering Journal, 2026)

FGF19 promotes cartilage destruction in the progress of temporomandibular joint osteoarthritis - Haoran Chen; Yujia Cui; Yi Liu; Caixia Pi; Jianing Wu; Jianxun Sun; Xian Liu; Tao Zuo; Jing Xie (Cell and Tissue Research, 2026)

Making waves: Overcoming toxicity and deactivation challenges in polymerization-based wastewater treatment - Pi-Jun Duan; Jun-Jie Huang; Chang-Wei Bai; Zhi-Quan Zhang; Xin-Jia Chen; Jing Wang; Fei Chen (Water Research, 2026)

Leveraging Mn(II)/UV/oxalic acid synergy for efficient and green Cr(VI) removal: Promoted Mn(II)/Mn(III) redox cycling and •CO₂− radical generation - Peng Xu; Changchao Pi; Jingwei Ma; Qiulai He; Mengqi Zheng; Jing Zou; John C. Crittenden (Chemical Engineering Journal, 2026)

The impact of hydrological regime changes induced by run-of-river hydroelectric stations on fish spawning - Jing Zhang; Wu Sha Ji Pi; Zi Jing Chen; Shi-Tao Peng; Bing Xing; Tao Lan; Er Di A Bi (Ecohydrology & Hydrobiology, 2025)

Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Weixia Zhi; Xinjie Guo; Yichu Nie; Lu Nie; Tingting He; Li Dai; Jing Xu; Xiangxin Zong; Jun Xu; Huaihong Cai; Yong Tang; Yanguang Cong; et al. (Chemical Engineering Journal, 2025)

Inversion of Rayleigh wave dispersion curves based on the Osprey Optimization Algorithm - Zhi Li; Hang-yu Yue; De-xi Ma; Yu Fu; Jing-yang Ni; Jin-jun Pi (Applied Geophysics, 2025)

Research Progress in Controlling Root Rot in Sugar Beet - Jing-Hao Li; Sheng-Nan Li; Zhi Pi; Ze-Dong Wu (Sugar Tech, 2025)

SERS-based lateral flow immunoassay for rapid and sensitive sensing of nucleocapsid protein toward SARS-CoV-2 screening in clinical samples - Weixia Zhi; Lingwei Wang; Li Dai; Jing Xu; Tingting He; Xiangxin Zong; Jun Xu; Huaihong Cai; Jiang Pi; Pinghua Sun; Shanze Chen; Xueqin Huang; et al. (Analytica Chimica Acta, 2025)

Genetic Diversity Analysis of 89 Monogerm Maintainer Lines of Sugar Beet - Jing-Jing Zhao; Lin-Lin Sun; Zhi Pi; Sheng-Nan Li; Ze-Dong Wu (Sugar Tech, 2025)

Composition, structure and comprehensive utilization of abalone shell: A review - Man-Yu Li; Yan-Chao Wu; Li Huang; Pi-Xian Gong; Hui-Jing Li (Sustainable Chemistry and Pharmacy, 2025)

Fe7C3 nanoparticles anchored on N-doped biochar as electrocatalyst for highly efficient oxygen evolution reaction - Wenhao Chen; Weitao Cao; Xinxin Pi; Zhen Liu; Zhiyang Li; Jian Li; Zhenyu Jing; Qiuju Du; Xiaoyong Lai; Yanhui Li (Fuel, 2024)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Fabrication of foxtail millet prolamin/caseinate/chitosan hydrochloride composite nanoparticles using antisolvent and pH-driven methods for curcumin delivery - Xiao Chen; Yan-Chao Wu; Liu-Hong Qian; Yu-He Zhang; Pi-Xian Gong; Wei Liu; Hui-Jing Li (Food Chemistry, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Janus fibrous membrane with directional liquid transport capacity for wound healing promotion - Haohong Pi; Yanli Xi; Jing Wu; Miaomiao Hu; Boyang Tian; Yiwen Yang; Rui Wang; Xiuqin Zhang (Chemical Engineering Journal, 2023)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

Impacts of Seagrass on Benthic Microalgae and Phytoplankton Communities in an Experimentally Warmed Coral Reef Mesocosm - Kwee Siong Tew; Jimmy Kuo; Jing-O Cheng; Fung-Chi Ko; Pei-Jie Meng; Anderson B. Mayfield; Pi-Jen Liu (Frontiers in Marine Science, 2021)
The effects of seagrass on microalgal assemblages under experimentally elevated temperatures (28°C) and CO 2 partial pressures (pCO 2 ; 800 μatm) were examined using coral reef mesocosms. Concentrations of nitrate, ammonium, and benthic microalgal chlorophyll a (chl-a) were significantly higher in seagrass mesocosms, whereas phytoplankton chl-a concentrations were similar between seagrass and seagrass-free control mesocosms. In the seagrass group, fewer parasitic dinoflagellate OTUs (e.g., Syndiniales) were found in the benthic microalgal community though more symbiotic dinoflagellates (e.g., Cladocopium spp.) were quantified in the phytoplankton community. Our results suggest that, under ocean acidification conditions, the presence of seagrass nearby coral reefs may (1) enhance benthic primary productivity, (2) decrease parasitic dinoflagellate abundance, and (3) possibly increase the presence of symbiotic dinoflagellates.

Drought tolerance in high-generation transgenic maize inbred lines overexpressing the betaine aldehyde dehydrogenase gene - He Zhao; Qi Zhang; Mo Zhang; Yu-Kun Jin; Zhen-Zhong Jiang; Nan Jiang; Qi Wang; Jing Qu; Shu-Yan Guan; Pi-Wu Wang (Cereal Research Communications, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Construction of a new plant expression vector and the development of maize germplasm expressing the Aspergillus ficuum phytase gene PhyA2 - Peng Jiao; Wen-Ya Yuan; Han-Dan Zhao; Jing Qu; Pi-Wu Wang; Shu-Yan Guan; Yi-Yong Ma (Genetic Resources and Crop Evolution, 2021)
Phytases, which belong to a special category of orthophosphoric monoester phosphohydrolases, degrade inositol hexaphosphate to produce lower-grade inositol phosphate derivatives and inorganic phosphate. Thus, phytases may improve phosphorus utilization, eliminate the anti-nutrient properties of phytic acid, and mitigate environmental pollution due to phosphorus contamination. In this study, we constructed a new root-specific expression vector by inserting the Aspergillus ficuum phytase gene PhyA2 into pCAMBIA3301-ZmGLU1P-Nos. The subsequent molecular analysis confirmed that six T 4 generation transgenic plants carried and expressed PhyA2 . A quantitative real-time PCR analysis indicated PhyA2 was highly expressed in the transgenic roots. Additionally, the phytase activity was 10.9-fold higher in the transgenic roots (peak activity of 5.432 U/g) than in the control roots. Moreover, compared with the control rhizosphere, the organic phosphorus content in the rhizosphere of the transgenic plants decreased significantly (by up to 5.21 mg/kg). An agronomic trait analysis indicated that PhyA2 expression can increase maize seed weight by up to 25.8 g. Therefore, the integration of PhyA2 into the maize genome can enhance the ability of maize plants to use the phosphorus compounds in soil, while also improving the plant growth status and increasing the seed yield.

Identification and characterization of two morphologically distinct stem cell subpopulations from human urine samples - An-Jing Chen; Jin-Kui Pi; Jun-Gen Hu; Yi-Zhou Huang; Hong-Wei Gao; Sheng-Fu Li; Jesse Li-Ling; Hui-Qi Xie (Science China Life Sciences, 2020)

Synthesis of natural product inulavosin via Ga(OTf) 3 -Catalyzed Hetero Diels–Alder Dimerization of salicyl alcohol derivative - Pi-Xian Gong; Hui-Jing Li; Meirong Wang; Yun-Fei Cheng; Yan-Chao Wu (Natural Product Research, 2019)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Mass spectrometry-guided isolation of two new dihydrobenzophenanthridine alkaloids from Macleaya cordata - Zhi-Xing Qing; Peng Yang; Kun Yu; Xue-Yi Yang; Jing-Hong Liu; Feng Xiang; Hua-Liang Cao; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2017)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

Impaired SIRT1 promotes the migration of vascular smooth muscle cell-derived foam cells - Ming-Jie Zhang; Yi Zhou; Lei Chen; Xu Wang; Yan Pi; Chun-Yan Long; Meng-Jiao Sun; Xue Chen; Chang-Yue Gao; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2016)

An overview of potential molecular mechanisms involved in VSMC phenotypic modulation - Ming-Jie Zhang; Yi Zhou; Lei Chen; Yan-Qin Wang; Xu Wang; Yan Pi; Chang-Yue Gao; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2016)

Assessment of ichthyotoxicity and anthropogenic contamination in the surface waters of Kenting National Park, Taiwan - Te-Hao Chen; Yi-Ling Chen; Chia-Yang Chen; Pi-Jen Liu; Jing-O Cheng; Fung-Chi Ko (Environmental Monitoring and Assessment, 2015)

Berberine protects homocysteic acid-induced HT-22 cell death: involvement of Akt pathway - Meihui Chen; Min Tan; Minghua Jing; Anmin Liu; Qinyu Liu; Shijun Wen; Ziwei Chen; Xiaojuan Chao; Xixin He; Charles Ramassamy; Youheng Gao; Rongbiao Pi (Metabolic Brain Disease, 2015)

Rapidly Dissolvable Microneedle Patches for Transdermal Delivery of Exenatide - Zhuangzhi Zhu; Huafei Luo; Wangding Lu; Hansen Luan; Yubo Wu; Jing Luo; Youjie Wang; Jiaxin Pi; Chee Yen Lim; Hao Wang (Pharmaceutical Research, 2014)

Association between estrogen receptor alpha c.454-397T>C and c.454-351A>G and ischemic stroke risk: a systematic review and meta-analysis - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Lu Guo; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing Xiang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Association between paraoxonase 2 Ser311Cys polymorphism and ischemic stroke risk: a meta-analysis involving 5,008 subjects - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Polysaccharides purified from the submerged culture of Ganoderma formosanum stimulate macrophage activation and protect mice against Listeria monocytogenes infection - Cheng-Li Wang; Chia-Chen Pi; Chu-Wei Kuo; Yu-Jing Zhuang; Kay-Hooi Khoo; Wen-Hsiung Liu; Chun-Jen Chen (Biotechnology Letters, 2011)

Using multiple-criteria decision-making techniques for eco-environmental vulnerability assessment: a case study on the Chi-Jia-Wan Stream watershed, Taiwan - Pi-Hui Huang; Jing-Shyan Tsai; Wen-Tzu Lin (Environmental Monitoring and Assessment, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Development of a molecular marker for specific detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Jing-Yi Chang; En-Tzu Liu; Chih-Ping Chao; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2009)

Protection effect of piper betel leaf extract against carbon tetrachloride-induced liver fibrosis in rats - Shun-Chieh Young; Chau-Jong Wang; Jing-Jing Lin; Pei-Ling Peng; Jui-Ling Hsu; Fen-Pi Chou (Archives of Toxicology, 2007)

Gaseous nitrogen oxide repressed benzo[a]pyrene-induced human lung fibroblast cell apoptosis via inhibiting JNK1 signals - Jing-Hsien Chen; Fen-Pi Chou; Hui-Hsuan Lin; Chau-Jong Wang (Archives of Toxicology, 2005)